REDUCTION OF LEAKAGE CURRENT IN GRID-CONNECTED PV SYSTEM (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Grid connections in the solar system have resulted in the revolution in the performance of the solar system and opened the doors of several opportunities to support the use of solar systems. The grid connected photovoltaic (PV) power systems are replacing the other systems very rapidly due to the better performance parameters like efficiency there by reducing the space requirement and cost of present systems. The grid connected system always faces the problems related to the safety and the job of the design engineer is to optimize the performance of the system. The decision makers have to work for addressing the issues related to the leakage current in such systems. Authors have discussed about the performance improvement by boost inverter inclusion in the conventional system. The near state pulse width modulation (NSPWM) is also included in the scope of this study under MATLAB /SIMULINK environment. The system performance was found improved and hence the study is helpful for improvement of the solar systems connected to the grid.